(untitled) (Journal of Forensic Medicine & Toxicology, 2014)
Determination of ‘time elapsed since death’ (TSD) is one of the important content of the post-mortem report. A recurring problem in forensic medicine is the need to fix the time of death within the limits of probability. The opinion of any doctor who offers a single time of death, instead of a range, must be viewed with suspicion (1). Investigators should consider the PMI as a minimum estimate of the time since death; never an absolute time since death (2). The points to be noted in ascertaining the time of death are warmth or cooling of the body, the absence or presence of cadaveric hypostasis, rigor mortis and the progress of decomposition.